Optimization of Emergency Handling Skills for Bleeding Through the Case Simulation Method for Adolescents: Optimalisasi Keterampilan Penanganan Kasus Kegawatdaruratan Perdarahan Melalui Case Simulation Method pada Remaja (JURNAL UNEJ, 2023)
Bleeding is damage to blood vessels so that blood comes out excessively from its original place. First aid in cases of bleeding is needed immediately before the victim gets medical assistance. Students are a vulnerable group to emergency events, so preparation of knowledge is needed on how to handle emergencies, one of which is when bleeding occurs. The purpose of this study was to increase the knowledge of SMK Trunojoyo Jember students about the concept of bleeding and first aid in dealing with bleeding cases. The method of providing education is carried out by means of a Case Simulation Method. Evaluation was carried out using a one group pre-post test design. The results obtained were that the students' knowledge of SMK Trunojoyo Jember regarding the concept and management of bleeding increased significantly (p-value <0.000). The Case Simulation Method has proven to be effective in increasing students' knowledge related to bleeding concepts and management because the material is easier to understand and students can actively participate in simulation sessions.